L-Phenylalanine Production by Stabilised Calcium Alginate Immobilised Aminoacylase - Siaw, Yew Seong (1993)
Enzymatic resolution of DL-amino acids using aminoacylase immobilised on DEAE-sephadex has been employed in the industry for the production of the optically active, L-amino acid There are,however, soeliitations to this technique. The aims of this study were to establish an efficient immobilisation method for aminoacylase and to report the preparation, properties, and applicability of the resulting immobilised aminoacylase. Aminoacylase was immobilised in calcium alginate beads(ACAG). The ACAG was further stabilised by coating with polyethyleneimine (PEI), a mixture of polyethyleneimine and glutaraldehyde(PEI-GLU), poly-L-lysine (PLL), or by cross - linking with carbodiimide. Each type of the immobilised aminoacylase was then used to perform the optical resolution of N-acetyl-DL-phenylalanine.